"Mini-Flow-Through" Deep Inferior Epigastric Perforator Flap for Breast Reconstruction with Preservation of Both Internal Mammary and Deep Inferior Epigastric Vessels - Toshihiko Satake; Jun Sugawara; Kazunori Yasumura; Taro Mikami; Shinji Kobayashi; Jiro Maegawa (Archives of Plastic Surgery, 2015)
This procedure was developed for preservation of the rectus muscle components and deep inferior epigastric vessel after deep inferior epigastric perforator (DIEP) flap harvesting. A 53-year-old woman with granuloma caused by silicone injection underwent bilateral nipple-sparing mastectomies and immediate reconstruction with "mini-flow-through" DIEP flaps. The flaps were dissected based on the single largest perforator with a short segment of the lateral branch of the deep inferior epigastric vessel that was transected as a free flap for breast reconstruction. The short segments of the donor deep inferior epigastric vessel branch are primarily end-to-end anastomosed to each other. A short T-shaped pedicle mini-flow-through DIEP flap is interposed in the incised recipient's internal mammary vessels with two arterial and four concomitant venous anastomoses. Although it requires multiple vascular anastomoses and a short pedicle for the flap setting, the mini-flow-through DIEP flap provides a large pedicle caliber, enabling safer microsurgical anastomosis and well-vascularized tissue for creating a natural breast without consuming time or compromising the rectus muscle components and vascular flow of both the deep inferior epigastric and internal mammary vessels.